Peramalan Pencemaran Udara di Kota Pekanbaru Menggunakan Metode Box-Jenkins - Ari Pani Desvina; Syahrul Ramadhan (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
This paper discusses the forecasting model of air quality in Pekanbaru by parameters of sulfurdioxide   SO2 by using Box-Jenkins. The procedure of determine the forecasting model by using Box-Jenkins method that used stationary data, if was not stationary, it need differencing process, identificationmodel of ACF and PACF, parameter estimation, verification models by looking residual result, andconducted the forecasting stage. The daily data used for the establishment of forecasting model was thedata from 24 November 2014 to 10 February 2015. The results showed that ARIMA(1,1,0) with modelXt  0.4063Xt1  0.5937Xt2  at was a appropriate model to forecasting process. Forecasting resultsindicated that the air quality increase if compared to the previous time, because the trend of the data airquality followed data format of trend up.Keywords: ARIMA, Box-Jenkins, Sulfur Dioxide